Echocardiographic Assessment of Cardiac Structural and Functional Indices in Broiler Chickens Treated with Silver Nanoparticles. (27th October 2013) - Raieszadeh, Hamid; Noaman, Vahid; Yadegari, Mehrdad
Abstract : 270 Ross broiler chickens of twenty days old were housed in 18-floor pens in a completely randomized design with six treatment groups and three replicate groups and fifteen chicks per each pen. The treatment groups (1–6) consisted of 0, 10, 20, 30, 50, and 70 ppm of nanocide in drinking water, respectively. At 26 days of age, 3 chickens were selected randomly for echocardiography using a 7.5 MHz linear probe, and the left ventricular internal diameter at the end of diastole (LVIDd), left ventricular internal diameter at the end of systole (LVIDs), left ventricular fractional shortening (LVFS), ejection fraction (EF), stroke volume (SV), interventricular septum thickness at the end of systole (IVSTs), and interventricular septum thickness at the end of diastole (IVSTd) were evaluated. LVIDd and LVIDs in group six were of higher rate than other groups and showed statistically significant differences with groups two, three, and four (P < 0.05 ). LVFS, percentage of EF, and IVSTd were minimum in group six and had significant difference with other groups (P < 0.05 ). The results of this study showed that prescription of high dosage of nanocide leads to cardiovascular problems with decrease in myocardial contractility and increase in the internal diameter of left ventricle.